2021
DOI: 10.1021/acsanm.1c01991
|View full text |Cite
|
Sign up to set email alerts
|

Selective Photothermal Reduction of CO2 to CO over Ni-Nanoparticle/N-Doped CeO2 Nanocomposite Catalysts

Abstract: Photothermal reverse water gas shift reaction is one of the promising methods to palliate global energy and environmental issues. Searching for catalysts with high activity and CO selectivity for CO 2 conversion has been attracting extensive attention. In this work, Ni nanoparticleloaded N-doped CeO 2 (Ni/N-CeO 2 ) composite catalysts were synthesized using a three-step method. Under light irradiation, the optimal Ni/N 5.0 -CeO 2 exhibited a CO yield rate of 20.9 mmol• g cat −1 •h −1 with almost 100% of CO sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…As shown in Fig. 8, the intermediates appeared with the reaction: monodentate carbonate ( m -CO 3 2− , 1519 and 1457 cm −1 ), 19,53,54 bicarbonate (HCO 3 − , 1650 and 1540 cm −1 ), 54–56 CO 2 − (1681 cm −1 ), 27 and chelating bridging carbonate ( c -CO 3 2− , 1704 cm −1 ). 17 The bands detected at 1558 cm −1 and 1509 cm −1 could be assigned to the asymmetric vibration of the formate OCO group 57 and CO stretching, 58,59 respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As shown in Fig. 8, the intermediates appeared with the reaction: monodentate carbonate ( m -CO 3 2− , 1519 and 1457 cm −1 ), 19,53,54 bicarbonate (HCO 3 − , 1650 and 1540 cm −1 ), 54–56 CO 2 − (1681 cm −1 ), 27 and chelating bridging carbonate ( c -CO 3 2− , 1704 cm −1 ). 17 The bands detected at 1558 cm −1 and 1509 cm −1 could be assigned to the asymmetric vibration of the formate OCO group 57 and CO stretching, 58,59 respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Photothermal catalytic systems are considered to be one of the most promising ways to achieve solar fuels under mild conditions. 2,9,15,16 Many transition metal nanoparticles such as Fe, 17 Co, 7,18 Ni, 19,20 and Cu [21][22][23] have been reported to have RWGS photothermal catalytic activity, but still face the problem of low product selectivity with the main by-product being CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…When DPC-C4-Ni was compared with some of the best-reported photocatalysts (plasmonic and semiconducting) for CO 2 to CO conversion, we found that DPC-C4-Ni shows a high production rate and high stability (Figure S24 and Table S1). Our catalyst showed 2464 ± 40 mmol g Ni –1 h –1 CO production, i.e., ∼182 times higher (in the flow) (Table S1), using only light without any external heating.…”
Section: Resultsmentioning
confidence: 95%
“…15 Recently, many researchers loaded Ni on the photothermal catalyst CeO 2 ; the photoactivation effect and enrichment of electrons from Ni as well as the heating effect from solar light could increase the surface temperature of the catalyst, thus stabilizing the photothermal performance. 16,17 Ni, as a non-precious metal, also acted as an electron transfer channel.…”
Section: Introductionmentioning
confidence: 99%